Overwater Turbulence Intensity during Hurricane Katrina and Typhoon Russ (Global Journal of Science Frontier Research, 2015)
When Hurricane Katrina was over the Gulf of Mexico in 2005 an unprecedented significant wave height ( ) of 17 m was measured at the National Data Buoy Center (NDBC) station 42040. Using this extreme value and those from NDBC Buoy 42003 in the Gulf of Mexico during Katrina and Buoy 52009 during Typhoon Russ near Guam in the Pacific in 1990, it is found that approximately 85% of the variation in turbulence intensity (TI) over the wind seas can be explained by the variation in . Application of this relation between TI and shows that the estimated drift velocity is in excellent(over 95%) agreement with that measured during Hurricane Ivan.
Keywords: hurricane katrina - power law wind profile - roughness length - turbulence intensity - typhoon russ